Occurrence of alk(en)ylresorcinols in the fruits of two mango (Mangifera indica L.) cultivars during on-tree maturation and postharvest storage - Stefanie Kienzle (2018)
Regarding their relevance for the fungal resistance of mangoes in long supply chains, the alk(en)ylresorcinols (AR) were quantitated in peel and mesocarp throughout storage (27 days, 14 °C, ethylene absorption). The 12 'Chok Anan' and 11 'Nam Dokmai #4' lots picked between 83 and 115 days after full bloom (DAFB) had different harvest maturity indices. The development of dry matter and fruit growth indicated physiological maturity ∼100 DAFB. During storage, all fruits ripened slowly, mostly until over-ripeness and visible decay. The total AR contents always ranged at 73 ± 4.5 and 6.4 ± 0.7 mg hg -1 of 'Chok Anan' and 'Nam Dokmai #4' peel dry weight, respectively, but only at 6.7 ± 0.7 and 0.9 ± 0.1 mg hg -1 for the corresponding mesocarp (P ≤ 0.05). These narrow concentration ranges were contradictory to the decreasing fungal resistance. Accordingly, the alk(en)ylresorcinols have not been a deciding factor for the fungal resistance. © 2013 American Chemical Society.